Pergeseran Struktur Ekonomi Kota Bitung : Sektor Mana Yang Muncul Sebagai Penggerak Utama? - Rheza Auliya Rahman (Jurnal Pajak dan Keuangan Negara (PKN), 2025)
To achieve success in economic development, regional governments need to evaluate the economic conditions in their areas. This step aims to ensure that policies implemented can optimize the development of potential economic sectors. This study aims to identify leading sectors, explore the potential of specific sectors, and analyze changes in the economic structure of Bitung City during the 2014–2023 period. The approach used is quantitative descriptive, utilizing secondary data in the form of time series data from the Gross Regional Domestic Product (GRDP) of Bitung City from 2014 to 2023. The analysis was conducted using the Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Shift Share methods. The results show that the transportation and warehousing sector is a leading sector in Bitung City based on the intersection of these three analyses.